Irish Diaspora Business Elite philanthropy: boon or bane? - Anne Groutel (Revue LISA)
This paper deals with diaspora philanthropy in the Irish context. The first part looks at the enduring relationship between the Irish diaspora and the homeland illustrated by the huge amounts of money sent throughout the years by Irish emigrants to their relatives and the activities of diaspora philanthropic organisations in recent decades. Irish-American philanthropist and businessman, Charles F. Feeney, better known as Chuck Feeney, has made an outstanding contribution to Irish higher education through his foundation, The Atlantic Philanthropies. This article examines the far-reaching effects on the Irish economy of Feeney’s endowment – including his attempt to meddle in Ireland’s internal affairs seen as a threat in political circles, which somewhat soured the relationship he entertained with the Irish authorities.